2018
DOI: 10.1016/j.celrep.2018.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Structures of Eastern Equine Encephalitis Virus Reveal Mechanisms of Virus Disassembly and Antibody Neutralization

Abstract: SummaryAlphaviruses are enveloped pathogens that cause arthritis and encephalitis. Here, we report a 4.4-Å cryoelectron microscopy (cryo-EM) structure of eastern equine encephalitis virus (EEEV), an alphavirus that causes fatal encephalitis in humans. Our analysis provides insights into viral entry into host cells. The envelope protein E2 showed a binding site for the cellular attachment factor heparan sulfate. The presence of a cryptic E2 glycan suggests how EEEV escapes surveillance by lectin-expressing myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(112 citation statements)
references
References 93 publications
6
103
1
1
Order By: Relevance
“…It was shown previously (Gale 2019) that ΔS a_immob is the sum of the changes in translational entropy (ΔS trans ) and rotational entropy (ΔS rot ) of the whole virus on binding. According to Mammen et al (1998) Examples of diameters for arboviruses are ~50 nm for WNV (Mukhopadhyay et al 2003) and DENV, 66 nm for Eastern equine encephalitis virus (Hasan et al 2018) with BTV being slightly larger at 85 nm (Nason et al 2004). In contrast, HIV is much larger with a mean diameter of 134 nm in the case of mature HIV virions containing a single core (Briggs et al 2003 the number of CD4 + T cells in 1 mm 3 of blood with bound virus, C.V T is calculated for the HIV model using values of ΔS a_immob which decrease in steps of 18.6% from -240 J/mol/K (i.e.…”
Section: Effect Of Virus Size On the Magnitude Of δS A_immobmentioning
confidence: 99%
“…It was shown previously (Gale 2019) that ΔS a_immob is the sum of the changes in translational entropy (ΔS trans ) and rotational entropy (ΔS rot ) of the whole virus on binding. According to Mammen et al (1998) Examples of diameters for arboviruses are ~50 nm for WNV (Mukhopadhyay et al 2003) and DENV, 66 nm for Eastern equine encephalitis virus (Hasan et al 2018) with BTV being slightly larger at 85 nm (Nason et al 2004). In contrast, HIV is much larger with a mean diameter of 134 nm in the case of mature HIV virions containing a single core (Briggs et al 2003 the number of CD4 + T cells in 1 mm 3 of blood with bound virus, C.V T is calculated for the HIV model using values of ΔS a_immob which decrease in steps of 18.6% from -240 J/mol/K (i.e.…”
Section: Effect Of Virus Size On the Magnitude Of δS A_immobmentioning
confidence: 99%
“…Many alphavirus neutralizing antibodies in complex with virions have been studied by cryo-EM. These studies have shown that most of these neutralizing mAbs target the exposed E2 protein cap Hasan et al, 2018b;Long et al, 2015;Porta et al, 2016;Sun et al, 2013). One of the first studies produced four $15-Å resolution cryo-EM structures of CHIKV VLPs complexed with the Fab fragments of neutralizing mouse MAbs (Sun et al, 2013).…”
Section: Neutralizationmentioning
confidence: 99%
“…While both Fab fragments neutralize by stabilizing E2 trimeric spikes and preventing the viral fusion, the F5 cross-links E2 within a trimeric spike to block the receptor binding site, whereas the 3B4C-4 Fab cross links E2 from neighboring spikes to prevent the exposure of the fusion loop by steric hindrance (Porta et al, 2014). Recent cryo-EM studies looking at the SINV-EEEV chimera in complex with five different Fabs have revealed that three Fab fragments of neutralizing mAbs (EEEV-5, >EEEV-42 and EEEV-58) bound to domain A of E2 protein, which cause intraspike crosslinking, while the other two (EEEV-3 and EEEV-69) interact only with domain B favoring interspike cross-linking (Hasan et al, 2018b).…”
Section: Neutralizationmentioning
confidence: 99%
“…Rossmann, Kuhn and colleagues carried out many studies of alpha and flaviviruses relating to their assembly, maturation, and immunological properties with numerous publications in these areas continuing into the last years of Michael's work (Figure ). Structures at near‐atomic resolution of isolated alpha and flaviviruses, in complex with neutralizing antibodies and as asymmetric reconstructions were determined by cryoEM alone following the availability of the direct electron detector …”
mentioning
confidence: 99%
“…Structures at near-atomic resolution of isolated alpha and flaviviruses, in complex with neutralizing antibodies and as asymmetric reconstructions were determined by cryoEM alone following the availability of the direct electron detector. [28][29][30] Michael's interest in dsDNA bacteriophage started in the mid-90s, collaborating with Dwight Anderson (University of Minnesota) and Tim Baker on a series of studies of Phi 29 that continued for more than a decade. Their first paper described the entire prolate head and associated tail machine at moderate resolution, providing a description of the quasi-symmetry associated with the head as well as the symmetry mismatch at the point of interaction between the 12-fold symmetric portal and pentavalent site of insertion in the head.…”
mentioning
confidence: 99%